Gerakan Peduli Lingkungan melalui Penanaman Pohon sebagai Program Pengabdian kepada Masyarakat di Desa Meunasah Panggoi, Kota Lhokseumawe - Fitria Akmal; Sarrah Kurnia Fadhillah; Ainol Mardhiah; Harinawati Harinawati; Cut Andyna; Jafaruddin Jafaruddin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
This community service program aimed to promote a community-based environmental care movement through the planting of productive trees in Meunasah Panggoi Village, Muara Dua District, Lhokseumawe City. The program was implemented over four weeks using a Community-Based Participatory (CBP) approach, actively involving local residents in the planning, observation, seedling procurement, tree planting, and initial maintenance stages. The observation results indicated that vegetation cover in the village was still limited, highlighting the need for sustainable greening efforts. A total of 25 productive trees, including mango, longan, coconut, guava, and avocado, were successfully planted at several strategic locations. The activity involved village officials, youth groups, and community members, thereby strengthening public participation in environmental conservation. The program not only increased vegetation cover but also reinforced the spirit of mutual cooperation, enhanced collective awareness of environmental preservation, and encouraged the productive use of available land. The productive trees are expected to provide long-term ecological, social, and economic benefits by improving environmental quality and generating harvests that can be utilized by the community. Therefore, community-based greening represents an effective strategy for supporting sustainable environmental development at the village level.